Pengaruh konflik peran, ambiguitas peran dan stres kerja terhadap kinerja karyawan - Nur, Ismi Rija; Hidayati, Tetra; Maria, Siti (JURNAL MANAJEMEN, 2016)
The purpose of this research is to know how big the influence of Role Conflict, Role Ambiguity and Job Stress on the Employees Performance at PT . Midi Utama Indonesia Tbk Branch Samarinda . The sample on this research is consist of 40 respondents which are chosen from the method of Accidental Sampling . The analyst means that is used in this research is the multiplied linear regression with the help of IBM program Statistical Product and Service Solution ( SPSS ) 22 For Windows. The results of this research shows that partially of the hypothesis with the t- test where X1 = -2.283 ; X2 = -4.290 ; X3 = 3.426 . The variable negative value of Role Conflict, Role Ambiguity on the Employees Performance and positve value Stress Of Work on the Employees Performance has a strong relationship.Keyword: Role Conflict , Role Ambiguity , Work Stress and Employee Performance.